Trends Research of Cerebral Palsy Football through a Bibliometric Analysis - Umar, Fadilah; Misbah, Misbah; Fadian, Ulfa Fatahara Laras; Mahakeeta, Ann (KnE Social Sciences, 2024)
This research used bibliometric analysis to examine trends in Cerebral Palsy Football (CPF) research from 2012 to 2023. Based on the keywords entered in the Scopus database, 48 documents were obtained. After filtering based on specific criteria (only articles from journals and the English language), and 43 documents remained. CPF publications have increased regularly from 2016 to 2022. Spain is the country with the most research in the field of CPF. The International Journal of Sports Physiology and Performance is a Scopus-indexed journal that publishes many articles on CPF. Based on the visualization results using VOSviewer, seven clusters were obtained, and in the last year, research on CPF has been related to clinical articles, physical performance, training, and disabled athletes. The results of this research can be used as foundational material for further research in the field of CPF. For example, there is a need for research on training for CPF Players to improve their performance. Keywords: bibliometric analysis, cerebral palsy football, trends research, disability sport